Influence of built environment on quality of life changes in African-American patients with non-metastatic breast cancer. (May 2020) - Schootman, M.; Perez, M.; Schootman, J.C.; Fu, Q.; McVay, A.; Margenthaler, J.; Colditz, G.A.; Kreuter, M.W.; Jeffe, D.B.
Abstract: Research links the built environment to health outcomes, but little is known about how this affects quality of life (QOL) of African American breast cancer patients, especially those residing in disadvantaged neighborhoods. Using latent trajectory models, we examined whether the built environment using Google Street View was associated with changes in QOL over a 2-year follow-up in 228 newly diagnosed African American breast cancer patients. We measured QOL using the RAND 36-Item Health Survey subscales. After adjusting for covariates, improvement in emotional well-being and pain over time was greater for women living on streets with low-quality (vs. high-quality) sidewalks. Highlights: Many African American breast cancer patients live on low sidewalk quality streets. High sidewalk quality had an impact on improvements in emotional well-being and pain. Sidewalk quality may affect changes in QOL via physical activity or stress.